O papel dos indicadores do índice de mobilidade urbana sustentável na fase de compreensão da problemática do processo de planejamento - Alves, Ana Flávia Brandão (2014)
This research investigated the role of each indicator of the Index for Sustainable Urban Mobility – I-SUM as a proxy for understanding problems of the urban mobility planning process. Thus, a theoretical basis was built on the aspects that led to the evolution from the traditional transportation planning process to the urban mobility one. It is understood that this process is divided into two phases, the understanding of the problems and the intervention in the issue. The first consists of stages which lead to the diagnosis. The second comprises the stages where actions are defined to solve the problems. The traditional transportation planning, mainly focused on the needs of car users, offering them infrastructure, considers the problems separately. The rapid urbanization and the increasing number of vehicles in major cities resulted in several negative impacts on the environment, leading to more complex problems and the current crisis of mobility. A paradigm shift was necessary, in this case, to the new concept of mobility planning. This involves aspects such as accessibility, sustainability, systemic approach and the use of performance indicators for analysis of urban scenarios. It is also recognized the need of mobility planning methods that comprehend this whole issue and its complexity in an attempt to find workable solutions to reverse the current situation. This dissertation proposed a systematic method for the problem understanding phase of the mobility planning. Mobility systems problems are identified with its cause and effect relations and the use of indicators is essential to highlight the reality of the various situations. I-SUM was chosen due to its comprehensive structure, composed of 87 indicators. It was developed intending to aid in evaluation, diagnosis and monitoring of urban mobility. It may also support the proposal of public policies towards sustainability. Its indicators were classified according to their utilities for the phases of the planning process, emphasizing those that help in the characterization and diagnose of problems. The classification consisted of a procedure that associated these indicators and the elements of a semantic network representing urban mobility. Over half of them were classified in the phase of problem understanding. This may facilitate the understanding of the complexity and give support to planners in the challenge of predict and prevent potential problems, leading to the anticipation of appropriate measures to alleviate the mobility difficulties.